Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fonc.2021.650562
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Inflammatory-Nutritional Prognostic Scoring System for Stage III Gastric Cancer Patients With Radical Gastrectomy Followed by Adjuvant Chemotherapy

Abstract: PurposeThe present study was designed to explore the prognostic value of preoperative inflammatory and nutritional biomarkers in stage III gastric cancer (GC) patients with adjuvant chemotherapy and to develop a novel scoring system called the inflammatory-nutritional prognostic score (INPS).MethodsA total of 513 patients with pathological stage III GC undergoing radical gastrectomy followed by adjuvant chemotherapy from 2010 to 2017 were enrolled in the study. Clinicopathological characteristics and blood tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 34 publications
(46 reference statements)
2
23
0
Order By: Relevance
“…The authors proved that INPS score has a good predicting performance for overall survival in stage III gastric cancer patients with radical surgery followed by adjuvant chemotherapy. 45 In our study, our results also showed that NLR was significantly associated with prolonged hospital stay and complication in univariate analysis. However, this association did not reach statistical significance in multivariate analysis.…”
Section: Discussionsupporting
confidence: 77%
“…The authors proved that INPS score has a good predicting performance for overall survival in stage III gastric cancer patients with radical surgery followed by adjuvant chemotherapy. 45 In our study, our results also showed that NLR was significantly associated with prolonged hospital stay and complication in univariate analysis. However, this association did not reach statistical significance in multivariate analysis.…”
Section: Discussionsupporting
confidence: 77%
“…Integration of multiple biomarkers could provide prognostic models with substantially higher predictive accuracy than that achieved with models based on one or a few inflammatory biomarkers. 12 , 21 , 37 But most of current studies simply combined candidate inflammatory parameters with strong collinearity and correlation into a multivariate Cox regression model to identify independent predictors, which can lead to conflict between parameters and certain statistical problems. 12 In this study, we performed the LASSO Cox regression analysis to include the maximal number of available inflammatory-nutritional biomarkers and effectively single out four valuable inflammatory indexes, namely, NLR, MLR, PNI, and AAPR; this approach could avoid the influence of multicollinearity to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the preoperative nutritional status was shown to affect the occurrence of postoperative surgical complications, toxicity of adjuvant treatment, and patient's survival in various malignancies [7][8][9][10]. Although several scoring system and serum biomarker have been tested, optimal nutritional biomarkers have not yet been established.…”
Section: Introductionmentioning
confidence: 99%